Influence of ceramic Kelvin Cell's strut shape on mechanical properties - Simon, Swantje; Köllner, David; Hoffmann, Patrizia; Keck, Elisabeth; Spath, Isabella; Meyse, Maximilian; Fey, Tobias (Open Ceramics, 2023)
The replica technique is one of the most established manufacturing methods of highly porous scaffolds for bone tissue engineering. Despite a multitude of possible templates, this method is limited in terms of reproducibility and periodicity. We overcome this issue by 3D-printing of designed periodic polymer templates with varying strut shape and thickness which we further process with the replica technique to obtain cellular ceramics with adjustable micro- and macrostructure. The periodic structure (Kelvin cells) was created using computer-aided design (CAD) software. These 3D rigid polymer structures were coated with alumina slurry and transformed to ceramic structures. This combination of polymer 3D-printing and the replica technique enables the application-specific production of cellular structures in a flexible and cost-effective process.
CRIS-Team Scopus Importer:2023-05-12
Keywords: Advanced replica technology; Kelvin cell; Periodic structure